The Magnificat and Online Gender-Based Violence: A Theological Framework for the Church’s Role in Digital Justice Advocacy - Lewar, Paulus Pati; Kleden, Fransiskus Bala; Sihombing, Adison Adrianus; Rizzi, Giovanni (UIN Sunan Gunung Djati Bandung, 2024)
: Online Gender-Based Violence (OGBV) has become an urgent global issue, exacerbated by technological advancements and the widespread use of digital platforms. This study explores the intersection of OGBV and biblical theology by analyzing Mary’s Magnificat as a framework for the Church’s response to digital gender injustices. The study aims to provide a theological perspective on OGBV, highlighting the role of the Church in advocating for digital justice and supporting survivors. Employing a qualitative descriptive approach, this research integrates biblical-theological analysis and literature review. The primary sources include the Magnificat (Luke 1:46-55), theological reflections on gender justice, and reports on OGBV from institutions such as Komnas Perempuan and SAFEnet. The study utilizes thematic analysis to examine how the Magnificat serves as a theological foundation for digital advocacy and ecclesial interventions. The findings indicate that the Magnificat is not merely a hymn of worship but a radical proclamation of justice, aligning with feminist and liberation theology. This study positions the Church as an ethical agent in digital governance, urging its involvement in advocacy, policy engagement, and pastoral care for OGBV survivors. Theologically, the research highlights the Church’s responsibility to challenge oppressive digital structures and promote gender justice in online spaces. This study contributes to digital theology by bridging biblical insights with contemporary discussions on gender-based violence in digital contexts. It also emphasizes the need for interdisciplinary collaboration between theologians, legal experts, and digital rights advocates to develop faith-based interventions against OGBV. However, further research is needed to expand theological engagement beyond the Magnificat and explore the role of other religious traditions in addressing OGBV.